Over a million students use our free study notes to help them with their homework
y = x^3+3x-2dy/dx = 3x^2-2Stationary points when dy/dx = 00 = 3x^2-22 = 3x^2+-root2 = 3x+-root2/3 = x
Area isosceles = hb/2 = hy/2Perimeter = 24x+3+x+3+x+2 = 243x + 8 = 243x = 16x = 16/3h^2 = (x+3)^2 - ((x+2)/2)^2h^2 = 56h = 2 root14area = 2root14*(x+2)/2area = 13.719 to 1dp
First begin with rearranging the second equation to put it in terms of Y. Then substitute by putting the second equation (y=3x+13) into equation one as Y^2. Expand (3x+13)^2 and add like terms to form 10x...
Factorising gives: y = (x+2)(x+1) = 0. y only equals 0 when (x+2)=0 or (x+1)=0. Therefore x=-2 or x=-1
4^(n)-1 factors to (2^(n)-1)(2^(n)+1) by difference of two squares by definition of a prime (only has factors 1 and itself (given that itself isn't 1))So Exactly one of the brackets should = 1 for 4^(n)-1...
←
671
672
673
674
675
→
Internet Safety
Payment Security
Cyber
Essentials